Pengaruh Pembelajaran Pendidikan Kewarganegaraan terhadap Karakter Siswa SMA: A Schematic Literature Review - Nifin Abdullah Al Jabri (Literaksi: Jurnal Manajemen Pendidikan, 2023)
A systematic literature review of 4 (four) studies on the impact of civics education on student character is the goal of the article's abstract. The purpose is to describe, make recommendations for how the article should be assessed, and highlight shared viewpoints in the article. A systematic literary analysis of 4 (four) pieces that address the impact of civics education on senior high school pupils was employed as the methodology. The review's findings indicate that four articles—namely, the impact of social media on middle and upper school students' character development, the moral decay of millennials brought on by their imitation of Western culture, the existence of heredity or the inheritance of traits, and the occurrence of excessive use of technology—show comfort fast in a variety of sectors, particularly in the fields of communication and technology.